(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Preparing students to be ready to collaborate in the 4.0 era using available curriculum implementation is one of the teachers’ tasks in the classroom. One of the problems that occurs at the Seboropasar State Elementary School in Purworejo district is that students’ collaboration skills are still low. For this reason, the introduction of a gamification-based learning model can be the right solution. The aim of this activity is to improve teachers’ understanding, knowledge, abilities and skills in carrying out interesting and interactive learning using a gamification approach. The method used in this activity is service learning with 3 stages, namely preparation, implementation and evaluation. This activity was attended by teachers and students Seboropasar State Elementary School teachers. The results obtained from this activity are increased understanding, abilities and skills of teachers in managing learning that is interactive, interesting and able to improve students’ collaboration abilities.